Risk of hepatitis C virus transmission from patients to surgeons: model based on an unlinked anonymous study of hepatitis C virus prevalence in hospital patients in Glasgow. Issue 9 (11th August 2003) - Thorburn, D; Roy, K; Cameron, S O; Johnston, J; Hutchinson, S; McCruden, E A B; Mills, P R; Goldberg, D J
Abstract : Background: The risk of a surgeon acquiring the hepatitis C virus (HCV) through occupational exposure is dependant on the prevalence of HCV infection in the patient population, the probability of a percutaneous injury transmitting HCV, and the incidence of percutaneous injury during surgery. Aims: To estimate the prevalence of HCV infection in the adult surgical patient population in North Glasgow and thereafter estimate the risk of HCV transmission to surgeons through occupational exposure. Methods: The prevalence of HCV infection was estimated through the unlinked anonymous testing of samples from male surgical patients, aged 16–49 years, in two North Glasgow hospitals from 1996 to 1997, and adjusting these data for age and sex. Using published estimates of the incidence of percutaneous injury during surgery and percutaneous injury transmitting HCV, the risk of occupational transmission of HCV to surgeons was then derived. Results: The estimated prevalence of anti-HCV infection for all adult patients in the two hospitals combined was 1.4% (cardiothoracic/cardiology 0.8%, orthopaedics/rheumatology 1.4%, general surgery/ENT 2.0%). The estimated probability of HCV transmission from an HCV infected patient to an uninfected surgeon was 0.001–0.032% per annum (0.035–1.12% risk over a 35 year professional career). Conclusions: The risk of an individual surgeon acquiring HCV through occupational exposure is low, even in an area with an extremely high prevalence of HCV among its injecting drug using population. Surgeons however should be encouraged to observe universal precautions and present for assessment after needlestick injuries to protect themselves and their patients from this insidious infection.